Emotional Communication in Speech and Music: The Role of Melodic and Rhythmic Contrasts - Quinto, Lena R.; Thompson, William F.; Keating, Felicity L. (Frontiers in Psychology, 2013)
Many acoustic features convey emotion similarly in speech and music. Researchers have established that acoustic features such as pitch height, tempo, and intensity carry important emotional information in both domains. In this investigation, we examined the emotional significance of melodic and rhythmic contrasts between successive syllables or tones in speech and music, referred to as Melodic Interval Variability (MIV) and the normalized Pairwise Variability Index (nPVI). The spoken stimuli were 96 tokens expressing the emotions of irritation, fear, happiness, sadness, tenderness or no emotion. The music stimuli were 96 phrases, played with or without performance expression and composed with the intention of communicating the same emotions. Results showed that speech, but not music, was characterized by changes in MIV as a function of intended emotion. Music and speech were both characterized by changes in nPVI as a function of intended emotion. The results suggest that these measures may signal emotional intentions differently in speech and music.